Genetics and the Clinical Approach to Paragangliomas - Schulte, K.-M.; Talat, N.; Galata, G.; Aylwin, S.; Izatt, L.; Eisenhofer, G.; Barthel, A.; Bornstein, S. R. (Hormone and Metabolic Research, 2014)
This study analyses new information on gene mutations in paragangliomas and puts them into a clinical context. A suspicion of malignancy is critical to determine the workup and surgical approach in adrenal (A-PGL) and extra-adrenal (E-PGL) paragangliomas (PGLs). Malignancy rates vary with location, family history, and gene tests results. Currently there is no algorithm incorporating the above information for clinical use. A sum of 1 821 articles were retrieved from PubMed using the search terms “paraganglioma genetics”. Thirty-seven articles were selected of which 9 were analyzed. It was found that 599/2 487 (24%) patients affected with paragangliomas had a germline mutation. Of these 30.2% were mutations in SDHB, 25% VHL, 19.4% RET, 18.4% SDHD, 5.0% NF1, and 2.0% SDHC genes. A family history was positive in 18.1–64.3% of patients. Adrenal PGLs accounted for 55.1% in mutation (+) and 81.0% in mutation (−) patients (RR 1.2, p<0.0001). Bilateral A-PGLs accounted for 56.4% in mutation (+) and 3.2% in mutation (−) patients (RR 8.7, p<0.0001). E-PGL were found in 33.6% of mut+ and 17.3% of mut– (RR 1.7, p<0.0001). In mutation (+) patients PGLs malignancy varied with location, adrenal (6.4%) thoraco-abdominal E-PGL (38%), H & N E-PGL (10%). Malignancy rates were 8.2% in mutation (−) and lower in mutation (+) PGLs except for SDHB 36.5% and SDHC 8.3%. Exclusion of a mutation lowered the probability of malignancy significantly in E-PGL (RR 0.03 (95% CI 0.1–0.6); p<0.001). Mutation analysis provides valuable preoperative information to assess the risk of malignancy in A-PG and E-PGLs and should be considered in the work up of all E-PGL lesions.
Keywords: paraganglioma; cancer; malignancy; germline mutations